2006
DOI: 10.1353/aad.2006.0043
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Twenty Literacy, Science, and Mathematics Practices Used to Educate Students Who Are Deaf or Hard of Hearing

Abstract: The results of a multistep process to begin identifying best practices in deaf education are presented. To identify current practices, a survey was conducted of the literature, the Web sites of professional organizations, and states' education Web sites, which yielded a number of commonly discussed practices. Ten of the more highly cited practices in literacy instruction and 10 of the more highly cited practices in science and mathematics instruction were identified for additional scrutiny. Hundreds of article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 58 publications
0
34
0
1
Order By: Relevance
“…Alternative ways of making science accessible must be utilized through the promotion of teaching methods which engage the deaf learner and aid both cognitive and linguistic development. Easterbrooks and Stephenson (2006) and Wang (2011) identify that society today requires us to think critically and in the science education of deaf pupils it is vital that the students engage in activities which encourage the use of critical thinking skills. They recognize that good practice in deaf education today cannot take place in a curriculum that does not provide the opportunity for the deaf learner to develop higher order thinking skills.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative ways of making science accessible must be utilized through the promotion of teaching methods which engage the deaf learner and aid both cognitive and linguistic development. Easterbrooks and Stephenson (2006) and Wang (2011) identify that society today requires us to think critically and in the science education of deaf pupils it is vital that the students engage in activities which encourage the use of critical thinking skills. They recognize that good practice in deaf education today cannot take place in a curriculum that does not provide the opportunity for the deaf learner to develop higher order thinking skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is when these skills are utilized that the deaf child is able to fully understand a concept and apply their understanding to real-life problems. Easterbrooks and Stephenson (2006) go on to stress that there is sound evidence which shows that hands-on activities that encourage critical thinking and enquiry in science improves the understanding of abstract concepts but that research is lacking for younger deaf students. This review proposes that research takes a step towards filling that gap and seeks to raise awareness of the strategies needed to encourage argumentation in science to ensure that deaf students are able to argue, interpret, and solve problems in the classroom and beyond.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is seen that Easterbrooks and Stephenson (2006), after reviewing relevant articles in the literature, reported that 20 methods in reading, mathematics and science education were effective and evidence-based practices for hearing-impaired or deaf children. Of those 20 methods which were evidence-based, the use of technologies were determined to have been more effective in math and science education when compared to the education of reading skills.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…Επίσης η πλοήγηση κρίθηκε σκόπιμο να είναι γρήγορη και εύχρηστη με δυνατότητες επεξεργασίας και προσαρμογής στις ανάγκες των μαθητών κάθε αναπηρίας όπως για παράδειγμα να υπάρχει δυνατότητα απόδοσης του περιεχομένου του εκπαιδευτικού υλικού στην Ελληνική Νοηματική Γλώσσα (ΕΝΓ). Επιπλέον εξασφαλίστηκαν υπολογιστικές μονάδες βιντεοσκόπησης, δομές ανάπτυξης και επεξεργασίας για μετατροπή στην ΕΝΓ, εκπαιδευτική διερμηνεία (Barman & Stockton, 2002•Easterbrooks & Stephenson, 2006• Fajardo, Parra, Cañas, 2010, βιντεοσκόπηση του επιμορφωτικού υλικού και όλα τα απαραίτητα μέσα και υλικά για την αποτελεσματική χρήση του εν λόγω υλικού στο σχολείο. H ανάπτυξη της ιστοσελίδας έγινε πάνω σε πλατφόρμα Joomla με επιπλέον επεξεργασία και ανάπτυξη εφαρμογών σε γλώσσες προγραμματισμού php, html και javascript.…”
Section: μεθοδολογίαunclassified